Delamination-and electromigration-related failures in solar panelsa review - Hasan A.A.Q.; Alkahtani A.A.; Shahahmadi S.A.; Alam M.N.E.; Islam M.A.; Amin N. (MDPI AG, 2023)
The reliability of photovoltaic (PV) modules operating under various weather conditions attracts the manufacturers concern since several studies reveal a degradation rate higher than 0.8% per year for the silicon-based technology and reached up to 2.76% per year in a harsh climate. The lifetime of the PV modules is decreased because of numerous degradation modes. Electromigration and delamination are two failure modes that play a significant role in PV modules output power losses. The correlations of these two phenomena are not sufficiently explained and understood like other failures such as corrosion and potential-induced degradation. Therefore, in this review, we attempt to elaborate on the correlation and the influence of delamination and electromigration on PV module components such as metallization and organic materials to ensure the reliability of the PV modules. Moreover, the effects, causes, and the sites that tend to face these failures, particularly the silicon solar cells, are explained in detail. Elsewhere, the factors of aging vary as the temperature and humidity change from one country to another. Hence, accelerated tests and the standards used to perform the aging test for PV modules have been covered in this review. 2021 by the authors. Licensee MDPI, Basel, Switzerland.